Endothelial progenitor cells in systemic sclerosis: their possible role in angiogenesis - N. Fracchiolla; L. Moronetti Mazzeo; I. Silvestris; W. Maglione; D.P. Comina; M. Cortiana; N. Del Papa; F. Fantini; A. Cortelezzi (PAGEPress Publications, 2011)
Background: Recently, several studies have demonstrated the presence of circulating endothelial progenitors (CEPs) responsable for angiogenesis. Notably, these cells are able to migrate to ischemic tissues and differentiate in situ in mature endothelial cells. Aim of this study was to assess the presence of CEPs in the peripheral blood of patients with Sistemic Sclerosis (SSc) and evaluate their significance as an attempt of re-vascularization Material and methods: Samples of peripheral blood from 40 healthy subjects and 56 patients with SSc were studied. Five-parameter, 3-color flow cytometry was performed with a FACScan. CEPs were defined as CD45 negative, CD34 and CD133 positive. In addition, plasma levels of vascular endothelial growth factor (VEGF) and basic fibroblast growth factor (bFGF) were detected by commercial ELISA (R&D Systems). Results: Levels of CEPs (CD133+/CD34+/CD45-) were significantly higher in patients with SSc in comparison to HC (P = 0.01). No correlation was found between CEPs and any clinical parameter of disease neither activity score. CEPs were significantly higher in the group of patients with early disease, while their number decreased in the late phases of disease. Plasma levels of VEGF, but not bFGF, were significantly higher in SSc in comparison to HC (P<0.001) but no correlation was found between VEGF concentrations and CEP number. Conclusions: The presence of CEPs in patients with SSc suggest that sclerodermic hypoxic tissues could induce the mobilization of bone-marrow derived cells in an attempt to provided new vessels, in the early phase of the disease, at least.